Lithium manganese iron phosphate material and preparation method thereof, positive electrode material and lithium ion battery

By optimizing the ratio of Fe, Mn and doped elements and combining with carbon cladding, a lithium manganese iron phosphate material was designed, which solved the problem that existing lithiated phosphate materials were difficult to take into account high energy density and fast charging performance, and achieved suitable blending applications and high energy density effects.

CN119774576APending Publication Date: 2025-04-08HUIZHOU EVE POWER CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202412000207.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing lithiated phosphate materials are difficult to take into account high energy density and fast charging performance, and cannot meet the needs of blending applications.

Method used

By optimizing the ratio of Fe element, Mn element and doping element M, a material including a core of lithium manganese iron phosphate material and a carbon coating is designed, and a specific preparation method is used to form a positive electrode material with low impedance and high energy density.

Benefits of technology

It achieves low impedance, fast charging performance, high energy density and suitable performance for blending applications, meeting the needs of lithium-ion batteries for fast charging and discharging and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774576A_ABST
    Figure CN119774576A_ABST
Patent Text Reader

Abstract

The invention provides a lithium manganese iron phosphate material and a preparation method thereof, a positive electrode material and a lithium ion battery. The lithium manganese iron phosphate material comprises a lithium manganese iron phosphate material core and a carbon coating layer coating the surface of the lithium manganese iron phosphate material core, the chemical general formula of the lithium manganese iron phosphate material core is LiFexMnyM1-x-yPO4, x is more than or equal to 0.80 and less than 1, y is more than 0 and less than or equal to 0.20, and x + y is less than 1; m is selected from any one or more of a V element, a Si element, a Ge element, a Sn element and a Zn element; and the powder linear resistance of the lithium manganese iron phosphate material is 5-50m omega / mm. In the blending application, the lithium manganese iron phosphate material disclosed by the invention can better adapt to a charge-discharge platform of a ternary material, can meet the quick charge requirement of a wider SOC (State of Charge) interval, and has the properties of lower powder line resistance, excellent energy density, capacity, quick charge, safety and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a lithium iron manganese phosphate material and a preparation method thereof, a positive electrode material, and a lithium ion battery. Background Art

[0002] Lithium phosphate materials have advantages such as low cost and safety. Different types of lithium phosphate materials have different defects. For example, lithium iron phosphate materials have low energy density, while lithium iron manganese phosphate has low capacity, high impedance and weak fast charging performance. At the same time, the low energy density of phosphates is difficult to meet the needs of the next generation of battery systems. Mixing lithium phosphates with high-energy-density oxides such as nickel, cobalt and manganese to meet the needs of high energy density is one of the future directions, but the current voltage platform of lithium iron phosphate is low and does not match the lithiated metal oxides. The Mn element in lithium manganese iron phosphate is too high and has high impedance, which does not match the kinetics of ternary materials. Therefore, it is also difficult to meet the needs of blending applications. Therefore, it is urgent to develop a lithium phosphate material that is suitable for blending applications and takes into account both high energy density and fast charging performance. Summary of the invention

[0003] The main purpose of the present invention is to provide a lithium manganese iron phosphate material and a preparation method thereof, a positive electrode material, and a lithium-ion battery to solve the problem that the lithiated phosphate materials in the prior art are difficult to take into account both high energy density and fast charging performance and cannot meet the requirements of blending applications.

[0004] In order to achieve the above-mentioned object, according to one aspect of the present application, a lithium iron manganese phosphate material is provided, wherein the lithium iron manganese phosphate material comprises a lithium iron manganese phosphate material core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate material core; the chemical formula of the lithium iron manganese phosphate material core is LiFe x Mn y M 1-x-y PO4, wherein 0.80≤x<1, 0<y≤0.20, and x+y<1; M is selected from any one or more of V element, Si element, Ge element, Sn element and Zn element; and the powder line resistance of the lithium manganese iron phosphate material is 5-50mΩ / mm.

[0005] Furthermore, 0.85≤x≤0.95, 0.05≤y≤0.15, and M is V element and / or Si element.

[0006] Furthermore, the mass proportion of the carbon coating layer in the lithium manganese iron phosphate material is 0.6-1.9%; and / or the Dv50 particle size of the lithium manganese iron phosphate material is 0.2-1.5 μm, and / or the compaction density of the lithium manganese iron phosphate material is 2.5-2.7 g / m 3 .

[0007] According to another aspect of the present application, a method for preparing the above-mentioned lithium iron manganese phosphate material is provided, and the preparation method comprises: step S1, first mixing raw materials including a manganese source, an iron source, a lithium source and an acidic compound to obtain a slurry; and step S2, sequentially sand-milling, spray-granulating and sintering the raw materials including the slurry and the carbon source to obtain the lithium iron manganese phosphate material; wherein the acidic compound is selected from any one or more of H3VO4, H2SiO3, H2GeO3, H2SnO3 and H2ZnO2.

[0008] Furthermore, the above-mentioned step S1 also includes: step S11, performing a second mixing of the raw materials including the manganese source and the acidic compound to obtain slurry A; step S12, performing a third mixing of the raw materials including the iron source and the lithium source to obtain slurry B; and step S13, mixing the raw materials including slurry A and slurry B to obtain a slurry; wherein the solid content of slurry A is 20-50%; the solid content of slurry B is 30-60%; and / or the second mixing time is 180-360 min, and / or the third mixing time is 60-180 min.

[0009] Furthermore, the manganese source is selected from any one or more of Mn3O4, MnCO3 and MnSO4; and / or the iron source is nanoscale amorphous iron phosphate; and / or the lithium source is lithium carbonate and / or lithium phosphate; and / or the molar ratio of the manganese source to the acidic compound is 0.01-0.2:0.01-0.05, calculated based on the manganese element in the manganese source and the metal element and / or Si element in the acidic compound; and / or the molar ratio of the lithium source to the iron source is 1-1.02:0.8-1, calculated based on the lithium element in the lithium source and the iron element in the iron source.

[0010] Furthermore, in the above step S2, the raw materials including the slurry and the carbon source are sand-milled to obtain a mixture; the particle size of the mixture is 0.1-1.2 μm, and the sand-milling time is 120-360 min; and / or the carbon source is glucose and / or sucrose; and / or the mass ratio of slurry A, slurry B and carbon source is 3-5:93-96:1-2; and / or the sintering atmosphere is nitrogen, and / or the sintering temperature is 720-780°C, and / or the sintering time is 24-36 h.

[0011] According to another aspect of the present application, a positive electrode material is provided, which includes the above-mentioned lithium manganese iron phosphate material.

[0012] Furthermore, the positive electrode material also includes a nickel cobalt manganese oxide material, and the mass ratio of the lithium iron manganese phosphate material to the nickel cobalt manganese oxide material in the positive electrode material is 100:5-35.

[0013] According to another aspect of the present application, a lithium-ion battery is provided, including a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet includes a positive electrode material, and the positive electrode material is the positive electrode material mentioned above.

[0014] By applying the technical solution of the present application, the present application optimizes the ratio of Fe element, Mn element and doping element M within the above range, so that the lithium iron manganese phosphate material can have a lower impedance, thereby better meeting the demand for fast charging performance. The doping element M adopts the above-mentioned types, which can directionally optimize the lattice size of the Mn element, achieve higher capacity and lower impedance characteristics, and further improve the energy density. The lithium iron manganese phosphate material of the present application has a lower powder line resistance, so that it can meet the requirements of fast charging performance, high energy density and cycle performance. In addition, the lithium iron manganese phosphate material of the present application can not only be used alone, but also suitable for blending applications. In blending applications, the lithium iron manganese phosphate material of the present application can better adapt to the charging and discharging platform of the ternary material, meet the fast charging requirements of a wider SOC range, and have excellent energy density, capacity, fast charging and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0016] Figure 1 The charge and discharge curve of the lithium-ion battery prepared by the positive electrode material in Example 1 of the present application is shown. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0018] As analyzed in the background technology of this application, the lithium phosphate materials in the prior art have the problem of difficulty in balancing high energy density and fast charging performance and failing to meet the requirements of blending applications. In order to solve the above problems, this application provides a lithium manganese iron phosphate material and a preparation method thereof, a positive electrode material, and a lithium-ion battery.

[0019] In a typical embodiment of the present application, a lithium iron manganese phosphate material is provided, wherein the lithium iron manganese phosphate material comprises a lithium iron manganese phosphate material core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate material core; the chemical formula of the lithium iron manganese phosphate material core is LiFe x Mn y M 1-x-yPO4, wherein 0.80≤x<1, 0<y≤0.20, and x+y<1; M is selected from any one or more of V element, Si element, Ge element, Sn element and Zn element; and the powder line resistance of the lithium manganese iron phosphate material is 5-50mΩ / mm.

[0020] The present application optimizes the ratio of Fe element, Mn element and doping element M within the above range, so that the lithium iron manganese phosphate material can have a lower impedance, thereby better meeting the demand for fast charging performance. The doping element M adopts the above-mentioned types, which can directionally optimize the lattice size of the Mn element, achieve higher capacity and lower impedance characteristics, and further improve the energy density. The lithium iron manganese phosphate material of the present application has a lower powder line resistance, so that it can meet the needs of fast charging performance, high energy density and cycle performance. In addition, the lithium iron manganese phosphate material of the present application can not only be used alone, but also suitable for blending applications. In blending applications, the lithium iron manganese phosphate material of the present application can better adapt to the charging and discharging platform of the ternary material, meet the fast charging requirements of a wider SOC range, and have excellent energy density, capacity, fast charging and safety performance.

[0021] In order to further improve the fast charging performance and energy density of lithium manganese iron phosphate materials, in one embodiment of the present application, 0.85≤x≤0.95, 0.05≤y≤0.15, and M is V element and / or Si element.

[0022] In one embodiment of the present application, the mass proportion of the carbon coating layer in the lithium manganese iron phosphate material is 0.6-1.9%; and / or the Dv50 particle size of the lithium manganese iron phosphate material is 0.2-1.5 μm, and / or the compaction density of the lithium manganese iron phosphate material is 2.5-2.7 g / m 3 .

[0023] It is preferred to control the mass proportion of the carbon coating layer in the lithium iron manganese phosphate material within the above range, which helps to improve the structural stability of the lithium iron manganese phosphate material, thereby improving the high-rate performance of the lithium-ion battery, and thus better suited to fast charging and discharging scenarios. It is preferred to control the Dv50 particle size and compaction density of the lithium iron manganese phosphate material within the above range, which helps to improve the charging and discharging efficiency and cycle stability of the lithium-ion battery. Among them, the Dv50 particle size is the particle size value corresponding to the cumulative volume percentage of 50% in the particle size distribution of the granular material.

[0024] In another typical embodiment of the present application, a method for preparing the above-mentioned lithium iron manganese phosphate material is provided, and the preparation method comprises: step S1, first mixing raw materials including a manganese source, an iron source, a lithium source and an acidic compound to obtain a slurry; and step S2, sequentially sand-milling, spray-granulating and sintering the raw materials including the slurry and the carbon source to obtain the lithium iron manganese phosphate material; wherein the acidic compound is selected from any one or more of H3VO4, H2SiO3, H2GeO3, H2SnO3 and H2ZnO2.

[0025] By adding the above-mentioned types of acidic compounds for doping in step S1, since the acidic compounds have more active hydrogen bonds, they are more likely to react with the manganese source to form metal-oxygen bonds. On the one hand, the doping element and the manganese element can be combined through the first mixing, and the doping element can stabilize the manganese element, thereby reducing the influence of the manganese element on the impedance of the lithium iron manganese phosphate material, thereby improving the fast charging performance of the lithium iron manganese phosphate material; on the other hand, the doping element can optimize the lattice size of manganese phosphate, thereby achieving higher capacity and lower impedance characteristics, thereby improving the energy density of the lithium iron manganese phosphate material. Therefore, the lithium iron manganese phosphate material obtained by the above-mentioned preparation method can not only have both fast charging performance and high energy density, but also is suitable for blending applications.

[0026] In one embodiment of the present application, the above-mentioned step S1 also includes: step S11, mixing the raw materials including the manganese source and the acidic compound for the second time to obtain slurry A; step S12, mixing the raw materials including the iron source and the lithium source for the third time to obtain slurry B; and step S13, mixing the raw materials including slurry A and slurry B to obtain a slurry; wherein the solid content of slurry A is 20-50%; the solid content of slurry B is 30-60%; and / or the second mixing time is 180-360 min, and / or the third mixing time is 60-180 min.

[0027] By mixing the manganese source and the acidic compound separately in step S11, and controlling the time of the second mixing within the above range, it is helpful to make a part of the doped metal elements preferentially combine with the manganese element, thereby directionally optimizing the high impedance and high distortion characteristics of the manganese element, and then improving the fast charging and power characteristics of the lithium iron manganese phosphate material. The above-mentioned step-by-step mixing method is preferred, and the time of the third mixing, the solid content of slurry A and slurry B are controlled within the above range, which is conducive to the full reaction between the components, thereby improving the activity and stability of the lithium iron manganese phosphate material. It is preferred to perform the second mixing and the third mixing by ball milling in a coarse grinding tank. The doping element and the manganese element can be better combined by low-cost ball milling, thereby preparing a doped mixture with more uniform doping and higher strength.

[0028] In one embodiment of the present application, the manganese source is selected from any one or more of Mn3O4, MnCO3 and MnSO4; and / or the iron source is nanoscale amorphous iron phosphate; and / or the lithium source is lithium carbonate and / or lithium phosphate; and / or the molar ratio of the manganese source to the acidic compound is 0.01-0.2:0.01-0.05, calculated based on the manganese element in the manganese source and the metal element and / or Si element in the acidic compound; and / or the molar ratio of the lithium source to the iron source is 1-1.02:0.8-1, calculated based on the lithium element in the lithium source and the iron element in the iron source.

[0029] It is preferred to control the types of manganese source, acidic compound, iron source and lithium source, and the molar ratio of the manganese source and the acidic compound to the molar ratio of the lithium source and the iron source within the above range, which helps to effectively adjust the chemical composition of the lithium manganese iron phosphate material, thereby optimizing its electrochemical properties and lower impedance, and thus better meeting the needs of fast charging performance.

[0030] In one embodiment of the present application, in the above step S2, the raw material including the slurry and the carbon source is sand-milled to obtain a mixture; the particle size of the mixture is 0.1-1.2 μm, and the sand-milling time is 120-360 min; and / or, the carbon source is glucose and / or sucrose; and / or, the mass ratio of slurry A, slurry B and carbon source is 3-5:93-96:1-2; and / or, the sintering atmosphere is nitrogen, and / or, the sintering temperature is 720-780°C, and / or, the sintering time is 24-36 h.

[0031] Preferably, the sanding time and the type of carbon source are within the above range, which helps to form a more uniform carbon coating during the sanding process, thereby improving the conductivity of the lithium iron manganese phosphate material. Preferably, the mass ratio of slurry A, slurry B and carbon source is within the above range, which helps to accurately adjust the ratio of Fe, Mn and M elements and the quality of the carbon coating, so that the lithium iron manganese phosphate material achieves the best electrochemical performance. Preferably, the sintering atmosphere, sintering temperature and sintering time are within the above range, which helps to optimize the crystal structure of the lithium iron manganese phosphate material, thereby improving the conductivity and reducing the impedance, thereby improving the fast charging performance and energy density of the lithium iron manganese phosphate material.

[0032] In another typical embodiment of the present application, a positive electrode material is provided. The positive electrode material includes the above-mentioned lithium manganese iron phosphate material.

[0033] The positive electrode materials including the above-mentioned lithium manganese iron phosphate material can better adapt to the charging and discharging platform of the ternary material and meet the fast charging requirements of a wider SOC range.

[0034] In one embodiment of the present application, the positive electrode material further includes a nickel cobalt manganese oxide material, and the mass ratio of the lithium manganese iron phosphate material to the nickel cobalt manganese oxide material in the positive electrode material is 100:5-35.

[0035] In the blending application, the lithium iron manganese phosphate material and the nickel cobalt manganese oxide material of the present application are blended as the positive electrode material, and the mass ratio of the lithium iron manganese phosphate material and the nickel cobalt manganese oxide material in the positive electrode material is preferably controlled within the above range, which helps to further improve the fast charging performance and energy density of the lithium-ion battery, thereby better adapting to the charging and discharging platform.

[0036] In another typical embodiment of the present application, a lithium-ion battery is provided, including a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet includes a positive electrode material, and the positive electrode material includes the positive electrode material described above.

[0037] The lithium-ion battery including the above-mentioned positive electrode material has high energy density, good fast charging performance and cycle performance.

[0038] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0039] Example 1

[0040] Based on the manganese element in the manganese source and the metal element in the acidic compound, Mn3O4 and H3VO4 were mixed in a coarse grinding tank A for a second time for 240 minutes at a molar ratio of 0.15:0.05 to obtain slurry A, and the solid content of slurry A was 35%. At the same time, based on the lithium element in the lithium source and the iron element in the iron source, lithium carbonate and nano-scale amorphous iron phosphate were mixed in a coarse grinding tank B for a third time for 80 minutes at a molar ratio of 1:0.8 to obtain slurry B, and the solid content of slurry B was 45%. Slurry A and slurry B were mixed to obtain slurry, and glucose was added to the slurry and sand-milled for 240 minutes in a sand milling tank. The mass ratio of slurry A, slurry B and glucose was 5:94:1. After grinding to a target particle size of 0.5 μm, spray granulation and sintering at 750°C in a nitrogen atmosphere for 30 hours were carried out in sequence, and then crushed into particles with a Dv50 particle size of 1 μm. The particles are compacted under a pressure of 3T to obtain lithium manganese iron phosphate material LiFe 0.8 Mn 0.15 V 0.05 PO4, in which the mass proportion of the carbon coating in the lithium manganese iron phosphate material is 1.6%.

[0041] Lithium iron manganese phosphate material and lithium nickel cobalt manganese oxide material LiNi 0.8 Co 0.1 Mn 0.1 O2 is mixed in a mass ratio of 0.85:0.15 to obtain the positive electrode material.

[0042] Example 2

[0043] Based on the manganese element in the manganese source and the Si element in the acidic compound, MnCO3 and H2SiO3 were mixed in a coarse grinding tank A for a second time for 210 minutes at a molar ratio of 0.15:0.03 to obtain slurry A, and the solid content of slurry A was 20%. At the same time, based on the lithium element in the lithium source and the iron element in the iron source, lithium carbonate and nano-scale amorphous iron phosphate were mixed in a coarse grinding tank B for a third time for 90 minutes at a molar ratio of 1:0.82 to obtain slurry B, and the solid content of slurry B was 30%. Slurry A and slurry B were mixed to obtain slurry, and glucose was added to the slurry and sand-milled for 240 minutes in a sand mill. The mass ratio of slurry A, slurry B and glucose was 5:94:1. After grinding to a target particle size of 0.1 μm, spray granulation and sintering at 720°C in a nitrogen atmosphere for 36 hours were carried out in sequence, and then crushed into particles with a Dv50 particle size of 0.2 μm. The particles are compacted under a pressure of 3T to obtain lithium manganese iron phosphate material LiFe 0.82 Mn 0.15 Si 0.03 PO4, in which the mass proportion of the carbon coating in the lithium manganese iron phosphate material is 1.6%.

[0044] Lithium iron manganese phosphate material and lithium nickel cobalt manganese oxide material LiNi 0.8 Co 0.1 Mn 0.1 O2 is mixed in a mass ratio of 0.85:0.15 to obtain the positive electrode material.

[0045] Example 3

[0046] Based on the manganese element in the manganese source and the Si element in the acidic compound, MnCO3 and H2SiO3 were mixed for a second time in a coarse grinding tank A at a molar ratio of 0.07:0.03 for 180 minutes to obtain slurry A, and the solid content of slurry A was 50%. At the same time, based on the lithium element in the lithium source and the iron element in the iron source, lithium carbonate and nano-scale amorphous iron phosphate were mixed for a third time in a coarse grinding tank B at a molar ratio of 1:0.9 for 120 minutes to obtain slurry B, and the solid content of slurry B was 60%. Slurry A and slurry B were mixed to obtain slurry, and sucrose was added to the sand mill for 240 minutes. The mass ratio of slurry A, slurry B and glucose was 3:96:1. After grinding to the target particle size of 1.2μm, spray granulation and sintering at 780℃ in a nitrogen atmosphere for 24h were carried out in sequence, and then crushed into particles with a Dv50 particle size of 1.5μm. The particles are compacted under a pressure of 3T to obtain lithium manganese iron phosphate material LiFe 0.9 Mn 0.07 Si 0.03 PO4, in which the mass proportion of the carbon coating in the lithium manganese iron phosphate material is 1.6%.

[0047] Lithium iron manganese phosphate material and lithium nickel cobalt manganese oxide material LiNi 0.8 Co 0.1 Mn 0.1 O2 is mixed in a mass ratio of 0.85:0.15 to obtain the positive electrode material.

[0048] Example 4

[0049] The difference from Example 1 is that the mass ratio of slurry A, slurry B and glucose is 5:94:1.5, and finally lithium manganese iron phosphate material and positive electrode material are obtained, wherein the mass proportion of the carbon coating layer in the lithium manganese iron phosphate material is 1.9%.

[0050] Example 5

[0051] The difference from Example 1 is that the mass ratio of slurry A, slurry B and glucose is 5:94:3, and finally lithium iron manganese phosphate material and positive electrode material are obtained, wherein the mass proportion of the carbon coating layer in the lithium iron manganese phosphate material is 2.5%.

[0052] Example 6

[0053] The difference from Example 1 is that the solid content of slurry A is 50%, and the solid content of slurry B is 60%, and finally lithium manganese iron phosphate material and positive electrode material are obtained.

[0054] Example 7

[0055] The difference from Example 1 is that the solid content of slurry A is 55%, and the solid content of slurry B is 65%, and finally lithium manganese iron phosphate material and positive electrode material are obtained.

[0056] Example 8

[0057] The difference from Example 1 is that the sintering temperature is 780° C., the sintering time is 24 h, and finally lithium manganese iron phosphate material and positive electrode material are obtained.

[0058] Example 9

[0059] The difference from Example 1 is that the sintering temperature is 800° C., the sintering time is 20 h, and finally lithium manganese iron phosphate material and positive electrode material are obtained.

[0060] Example 10

[0061] The difference from Example 1 is that lithium manganese iron phosphate material is directly used as the positive electrode material.

[0062] Embodiment 11

[0063] The difference from Example 1 is that, based on the manganese element in the manganese source, based on the metal element in the acidic compound, based on the lithium element in the lithium source, based on the iron element in the iron source, Mn3O4, H3VO4, lithium phosphate and nano-scale amorphous iron phosphate are first mixed in a coarse grinding tank at a molar ratio of 0.15:0.05:1:0.8 for 320 minutes to obtain a slurry, and finally obtain a manganese iron phosphate lithium material LiFe 0.8 Mn 0.15 V 0.05 PO4 and positive electrode materials.

[0064] Comparative Example 1

[0065] Based on the lithium element in the lithium source, the iron element in the iron source, and the manganese element in the manganese source, lithium carbonate, nano-scale amorphous iron phosphate, and MnCO3 are mixed in a coarse grinding tank at a molar ratio of 1:0.5:0.5 for 240 minutes to obtain a slurry. The slurry and glucose are sand-milled for 240 minutes, and the mass ratio of the slurry to glucose is 99:1. After grinding to the target particle size of 0.5μm, spray granulation and sintering at 750℃ in a nitrogen atmosphere for 30h are carried out in sequence, and then crushed into particles with a Dv50 particle size of 1μm. The particles are compacted under a pressure of 3T to obtain lithium manganese iron phosphate material LiFe 0.5 Mn 0.5 PO4.

[0066] Lithium iron manganese phosphate material and lithium nickel cobalt manganese oxide material LiNi 0.8 Co 0.1 Mn 0.1 O2 is mixed in a mass ratio of 0.85:0.15 to obtain the positive electrode material.

[0067] Comparative Example 2

[0068] Lithium phosphate and nano-scale amorphous iron phosphate were mixed in a coarse grinding tank for 120 minutes at a molar ratio of 1:1 based on the lithium element in the lithium source and the iron element in the iron source to obtain a slurry. The slurry and glucose were sand-milled for 240 minutes, and the mass ratio of the slurry and glucose was 98:2. After grinding to the target particle size of 0.5 μm, spray granulation and sintering at 750 ° C in a nitrogen atmosphere for 30 hours were carried out in sequence, and then crushed into particles with a Dv50 particle size of 1 μm. The particles were compacted under a pressure of 3T to obtain lithium iron phosphate material LiFePO4.

[0069] Lithium iron manganese phosphate material and lithium nickel cobalt manganese oxide material LiNi 0.8 Co 0.1 Mn 0.1 O2 is mixed in a mass ratio of 0.85:0.15 to obtain the positive electrode material.

[0070] Comparative Example 3

[0071] The difference from Example 1 is that Mn3O4 and metal oxide V2O5 are mixed for the second time to obtain slurry A, and finally the lithium manganese iron phosphate material LiFe 0.8 Mn 0.15 V 0.05 PO4.

[0072] Lithium iron manganese phosphate material and lithium nickel cobalt manganese oxide material LiNi 0.8 Co 0.1 Mn 0.1 O2 is mixed in a mass ratio of 0.85:0.15 to obtain the positive electrode material.

[0073] Test method:

[0074] Positive electrode sheet: The positive electrode materials of the above examples and comparative examples, the binder PVDF and the conductive agent acetylene black were mixed in a mass ratio of 94:3:3, and NMP was added and stirred to form a positive electrode slurry. The viscosity of the positive electrode slurry was 6000 mPa.s, and the solid content of the positive electrode slurry was 50%. The positive electrode slurry was coated on an aluminum foil current collector and rolled to obtain a coating surface density of 200 g / m 2 , compacted density is 2.7g / m 3 The positive electrode.

[0075] Negative electrode sheet: The negative electrode material graphite, the conductive agent acetylene black, the binder sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) were mixed in a mass percentage of 94:1:2:3, and then the solvent deionized water was added and stirred to obtain the negative electrode slurry; the above negative electrode slurry was evenly coated on the two surfaces of the negative electrode current collector copper foil, and after drying, rolling and slicing, the coating surface density was 90g / cm 3 , compacted density is 1.6g / cm 3 The negative electrode.

[0076] Electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a molar concentration of 1 mol / L.

[0077] Battery cell assembly: The positive electrode, separator and negative electrode are stacked in sequence, then the tabs are welded and baked. After the moisture content is qualified, an appropriate amount of electrolyte is injected. After packaging, aging, formation and vacuum sealing, a lithium-ion battery is prepared.

[0078] Electrical performance test:

[0079] Cycle test: DCR test: After the lithium-ion battery is discharged to 50% capacity at room temperature, it is discharged at 2C for 10s (C is the rated capacity of the battery), the final voltage V1 before discharge is planned, the voltage V2 at the end of discharge is recorded, and the DCR value is recorded = (V1-V2) / 2C. The lithium-ion battery is placed in a 45°C constant temperature box, charged to 4.25V at 1C constant current and constant voltage, and cut off at 0.02C, followed by a 1C discharge cycle, recording the cycle capacity and average voltage, obtaining the number of cycles for 80% capacity retention, and recording the voltage drop.

[0080] Powder wire resistance test: Use ST2742b fully automatic powder resistance meter, according to GB / T 40007-2021, use four-probe method to test, take 1.5g lithium manganese iron phosphate material powder and put it into the mold, pressurize it with 1t pressure, record the thickness, current and voltage of the powder block, and test the resistance per unit length, which is the powder wire resistance.

[0081] Compacted density test: Use the punching module to punch out the electrode per unit area, weigh the mass of the electrode, and subtract the mass of the aluminum foil per unit area to get the mass of the positive electrode material. Measure the thickness of the positive electrode material and calculate the volume of the positive electrode material. The compacted density of the positive electrode material = the mass of the positive electrode material / the volume of the positive electrode material.

[0082] The above test results are shown in Table 1.

[0083] Table 1

[0084]

[0085]

[0086] in, Figure 1 is a charge and discharge curve of a lithium-ion battery prepared from the positive electrode material in Example 1, Figure 1 It can be seen that the lithium manganese iron phosphate material of the present application has a wider charge and discharge range, with no mutation in the 10% to 80% SOC range, and is more conducive to 10% to 80% fast charging.

[0087] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0088] The present application optimizes the ratio of Fe element, Mn element and doping element M within the above range, so that the lithium iron manganese phosphate material can have a lower impedance, thereby better meeting the demand for fast charging performance. The doping element M adopts the above-mentioned types, which can directionally optimize the lattice size of the Mn element, achieve higher capacity and lower impedance characteristics, and further improve the energy density. The lithium iron manganese phosphate material of the present application has a lower powder line resistance, so that it can meet the needs of fast charging performance, high energy density and cycle performance. In addition, the lithium iron manganese phosphate material of the present application can not only be used alone, but also suitable for blending applications. In blending applications, the lithium iron manganese phosphate material of the present application can better adapt to the charging and discharging platform of the ternary material, meet the fast charging requirements of a wider SOC range, and have excellent energy density, capacity, fast charging and safety performance.

[0089] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium manganese iron phosphate material, characterized in that: The lithium iron manganese phosphate material comprises a lithium iron manganese phosphate material core and a carbon coating layer coated on the surface of the lithium iron manganese phosphate material core; The chemical formula of the lithium manganese iron phosphate material core is LiFe x Mn y M 1-x-y PO4, wherein 0.80≤x<1, 0<y≤0.20, and x+y<1; M is selected from any one or more of V element, Si element, Ge element, Sn element and Zn element; the powder line resistance of the lithium manganese iron phosphate material is 5-50mΩ / mm.

2. The lithium iron manganese phosphate material according to claim 1, characterized in that: 0.85≤x≤0.95, 0.05≤y≤0.15, and M is V element and / or Si element.

3. The lithium iron manganese phosphate material according to claim 1 or 2, characterized in that: The mass proportion of the carbon coating layer in the lithium manganese iron phosphate material is 0.6-1.9%; and / or, the Dv50 particle size of the lithium manganese iron phosphate material is 0.2-1.5 μm, and / or, the compaction density of the lithium manganese iron phosphate material is 2.5-2.7 g / m 3 .

4. A method for preparing the lithium manganese iron phosphate material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, first mixing raw materials including a manganese source, an iron source, a lithium source and an acidic compound to obtain a slurry; and Step S2, sequentially sand-milling, spray-granulating and sintering the raw materials including the slurry and the carbon source to obtain the lithium iron manganese phosphate material; Wherein, the acidic compound is selected from any one or more of H3VO4, H2SiO3, H2GeO3, H2SnO3 and H2ZnO2.

5. The preparation method according to claim 4, characterized in that: The step S1 further comprises: Step S11, performing a second mixing of the raw materials including the manganese source and the acidic compound to obtain slurry A; Step S12, performing a third mixing of the raw materials including the iron source and the lithium source to obtain slurry B; and Step S13, mixing the raw materials including the slurry A and the slurry B to obtain the slurry; Wherein, the solid content of the slurry A is 20-50%; the solid content of the slurry B is 30-60%; And / or, the second mixing time is 180 to 360 minutes, and / or, the third mixing time is 60 to 180 minutes.

6. The preparation method according to claim 4 or 5, characterized in that: The manganese source is selected from any one or more of Mn3O4, MnCO3 and MnSO4; and / or, the iron source is nanoscale amorphous iron phosphate; and / or, the lithium source is lithium carbonate and / or lithium phosphate; And / or, the molar ratio of the manganese source to the acidic compound is 0.01-0.2:0.01-0.05, calculated based on the manganese element in the manganese source and the metal element and / or Si element in the acidic compound; And / or, the molar ratio of the lithium source to the iron source is 1-1.02:0.8-1, calculated based on the lithium element in the lithium source and the iron element in the iron source.

7. The preparation method according to claim 5, characterized in that: In the step S2, the raw material including the slurry and the carbon source is sand-milled to obtain a mixture; the particle size of the mixture is 0.1 to 1.2 μm, and the sand-milling time is 120 to 360 min; and / or, the carbon source is glucose and / or sucrose; and / or, the mass ratio of the slurry A, the slurry B and the carbon source is 3-5:93-96:1-2; And / or, the sintering atmosphere is nitrogen, and / or, the sintering temperature is 720-780° C., and / or, the sintering time is 24-36 hours.

8. A positive electrode material, characterized in that The positive electrode material comprises the lithium manganese iron phosphate material according to any one of claims 1 to 3.

9. The positive electrode material according to claim 8, characterized in that The positive electrode material also includes a nickel cobalt manganese oxide material, and the mass ratio of the lithium iron manganese phosphate material to the nickel cobalt manganese oxide material in the positive electrode material is 100:5-35.

10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet comprises a positive electrode material, characterized in that: The positive electrode material is the positive electrode material according to claim 8 or 9.

Citation Information

Cited By

  • Lithium manganese iron phosphate material, preparation method of the same, cathode material, and lithium-ion battery

    EP4818116A1

  • Lithium iron manganese phosphate material, preparation method therefor, positive electrode material, and lithium ion battery

    WO2026143898A1